Structural peculiarities of a truncated Vκ(III) immunoglobulin light chain in myeloma with light chain deposition disease - DECOURT, C (Blackwell Science Inc, 1996)
We report on the primary sequence of the monoclonal immunoglobulin light chain (LC) REV involved in myeloma-associated light chain deposition disease (LCDD). This sequence was deduced from that of the corresponding complementary (c)DNA in bone marrow plasma cells. Products of three independent amplifications by polymerase chain reaction (PCR) were sequenced and found to be identical. The κ mRNA encoding this N-glycosylated LC showed an overall normal structure consisting of a Vκ(III) segment rearranged to Jκ(II). Direct N-terminal amino acid sequencing of the circulating monoclonal IgA2,κ showed identity with the bone marrow-derived sequence. The κ-chain presented several unusual features affecting both the leader sequence and the variable (V) region. Four unique amino acid substitutions were found at positions -8, -3, -2 and -1 in the leader sequence and probably resulted in an unusual cleavage by signal peptidase, thus making the LC truncated by one residue and accounting for its unique hydrophobic N-terminus: Ile-Ile-Leu. Additional peculiarities were observed in the V region, including a Thr74 → Asn substitution creating a N-glycosylation site, and Thr53 → Ile, which was only reported once among human κIII chains, in another LCDD case, and may be of special significance at a position usually harbouring a polar amino acid.